2019
DOI: 10.1108/ijpcc-02-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of mobile sensing technologies for identifying medicines by people with visual disabilities

Abstract: Purpose People with visual impairments may have difficulty in identifying information, either on a bottle or package of medicine. As a result, many of them need the help of a third party to discern which medication they should take. In this perspective, this study aims to assist people with visual impairments to identify their medicine by using mobile sensing technologies. Design/methodology/approach The authors have developed three versions of a mobile application. They use three technologies, namely, near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 23 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…User participation in the final stages, namely for evaluating the solutions, was stated by 5 studies: 4 in usability testing [37, 4244] and 1 in field testing [45]. Involvement, both in the design and testing phases, was reported by 14 studies [23, 2628, 3335, 38, 41, 46–50]. Although, it is pertinent to point out that: on the one hand, some studies mention the involvement of the participants at the beginning and at the end of the process, but not in all the stages of the process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…User participation in the final stages, namely for evaluating the solutions, was stated by 5 studies: 4 in usability testing [37, 4244] and 1 in field testing [45]. Involvement, both in the design and testing phases, was reported by 14 studies [23, 2628, 3335, 38, 41, 46–50]. Although, it is pertinent to point out that: on the one hand, some studies mention the involvement of the participants at the beginning and at the end of the process, but not in all the stages of the process.…”
Section: Resultsmentioning
confidence: 99%
“…The use of user-centred evaluation tends to be more explicit, explained and applied in studies that used qualitative methods, such as behavioural observation, think aloud techniques, in-depth interviews, and focus groups, among others these kinds of evaluation methods allow the user’s perspective to be addressed early [21, 2327, 37–38, 40, 50]. The analysis of the context of use could determine the user’s needs against which the preliminary design solutions will be tested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of children with Down syndrome, the authors observed that virtual reality in Wii games proved beneficial in improving sensory and motor functions, compared to traditional rehabilitation. In another study, Façanha et al (2019) , seeing that people with vision problems may have difficulty accessing medications, worked on mobile applications that helped them identify medications. Such assistive technology has led to direct or indirect improvements in the medical conditions of disabled people.…”
Section: Introductionmentioning
confidence: 99%